AXIOLOGY ARBITRATION VALUE RULING IN THE CASE SETTLEMENT TRADE (Case Study Decision Of Supreme Court Number : 199 K / Pdt.Sus / 2012) - Salam, Safrin (Tadulako Law Review, 2016)
The existence of the Indonesian National Arbitration Board (BANI) in Indonesia that still exist to this day is one manifestation of diakomodasinya patterns of dispute resolution outside the court. Legal Considerations Application Reasons Cancellation Arbitral Article 70 of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution in Supreme Court Decision No. 199 K / Pdt.Sus / 2012 Relation Ensure Legal Certainty In the disputing parties are legal considerations of the cancellation decision was not all acceptance or rejection of the cancellation request arbitration decision based on legal grounds contained in Article 70 of Law No. 30 of 1999. Act No. 30 of 1999 on the ADR needs to be improved, especially the explanation of article 60 and article 70 which could lead to legal uncertainty for justice seekers among businesses in the dispute and the opportunity loss of trust businesses to resolve the dispute out of court through arbitration institution (the Arbitration Tribunal Ad-Hoc, BANI, etc.)